(3adSaI YbhHI GdRfG (B: s (3OQGSI JGQjNjI (B/ s - (3EjeGf GdSjO YQags; (3YGOd HSjhfi (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI(B.s, 1994)
(3JHOC gPg GdQSGdI HaUd JegjOj Yf LQjeI GdRfG Hjf GdLQjeI GdNGUI hGdLQjeI GdYGeI, Ke jCJj GdaUd GdChd Yf adSaI YbhHI GdRfG aj HYV GdTQGFY GdTQbjI GdbOjeI, hGdaUd GdKGfj Yf adSaI YbhjI GdRfG aj HYV GdTQGFY GdZQHjI(B.s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B1994.s
Keywords: (3adSaI GdbGfhf hJGQjNgs; (3adSaI YbhHI GdRfGs; (3YbhHI GdRfG ai eUQ GdaQYhfjIs; (3YbhHI GdRfG aj HdGO eG Hjf GdfgQjfs; (3YbhHI GdRfG aj GdbGfhf GdjhfGfjs; (3YbhHI GdRfG aj GdbGfhf GdQheGfjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 1994